Kedudukan Anak Yang Lahir Di Luar Pernikahan Di Tinjau Dari Kompilasi Hukum Islam - Tri Khartika Nurry; Emmi Rahmiwita Nasution; Irda Pratiwi (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
Article 99 in Compilation of Islamic Law which states that: a legitimate child is a child born in or as a result of a legal marriage and the result of fertilization of a legal husband and wife outside the womb and born by the wife, which means that the child is said to be legitimate when born from marriage official one. If it is said "children born as a result of a legal marriage there are no problems, but children born during this legal marriage will raise suspicion if this Article is linked to other Articles that allow pregnant women because adultery marries a man who impregnates". a marriage of a pregnant woman because of adultery with a man who impregnates her is a legal marriage. In this paper the author uses normative juridical research methods that approach the law. In this paper also raised two legal issues that are how the legal consequences of children born to pregnant women married according to the Compilation of Islamic Law and how the position of out of wedlock children is reviewed based on a compilation of Islamic Law. Based on this writing, it can be concluded that a child born outside of marriage only has a nasab relationship with his mother and his mother's family.